The Mediating Role of Culture: Servant Leadership and Faculty Loyalty in Saudi Public Universities - Alenazy, Hanan Muhaya; Alsulami, Agel Fara (Journal of Posthumanism, 2025)
This qualitative study explores the complex relationship between servant leadership and faculty loyalty in Saudi public universities. Drawing on semi-structured interviews with 30 faculty from 6 institutions, it examines how cultural dimensions (hierarchy, collectivism) inform attitudes toward servant leadership and subsequent loyalty. It illustrates a complicated relationship between leadership and faculty in this mostly unique higher education environment. The findings suggest the power of cultural factors to shape response to leadership style and faculty buy-in. Although societal, governance, and academic cultures in most countries align with servant leadership due to its holistic approach through civic engagement and emphasis on community and service-based cooperation, hierarchical structures and traditional university power dynamics are one of the few barriers to the study’s implementation. The study underscores the need for contextual sensitivity, but with concrete and fresh insights that could inform future bespoke leadership development strategies and processes in Saudi higher education in particular. It posits that servant leadership can enhance and develop a positive academic community, which is a contributing factor in achieving Saudi Vision 2030’s goals of human capital development.